A Systematic Review on Language Model Compression: Perspectives for Efficiency and Sustainability in Information Systems - Mesquita, Lair Anderson de P.; Oliveira, Saulo Anderson F. de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248723, 2026)
Research Context: The rapid adoption of Large Language Models (LLMs) offers unprecedented opportunities for Intelligent Information Systems. However, their high computational cost creates significant deployment barriers in resource-constrained environments. This limited access for smaller organizations and developing regions reinforces social and economic disparities in the adoption of those systems. Scientific and/or Practical Problem: LLMs demand excessive resources, which hinders their integration into sustainable INFORMATION SYSTEMS. Furthermore, there is a lack of systematic evidence on how compression affects robustness, factuality, and applicability in different contexts. Proposed Solution and/or Analysis: This work presents a systematic literature review analyzing 30 peer-reviewed studies on LLM compression methods. The review identifies trade-offs, evaluate empirical results, and highlight gaps for future research. Related IS Theory: We interpret computational efficiency and accessibility as strategic resources (Resource-Based View) that enable the development of sustainable, and equitable digital infrastructures. Research Method: This study follows PICO structure with inclusion/exclusion criteria to works published between 2018 and January 2025. It was centered around eight research questions addressing efficiency, robustness, hardware compatibility, knowledge preservation, hybridization, architectural adaptation, evaluation metrics, and industrial viability. Summary of Results: Our study shows that efficiency and system-focused methods are the most developed and investigated for LLM compression for training and inference efficiency. Among these techniques, quantization consistently outperforms pruning and error-based methods, balancing performance and design savings. However, research on robustness, generalization, and practical use remains limited. Recent advances in shared hardware designs show potential for scalability and lower power consumption. However, practical studies on the long-term sustainability, ethical issues, and social impacts of LLM compression are rare in current scientific literature. Contributions and Impact to IS area: This work contributes by mapping key challenges in LLM compression research, offering insights to design efficient, sustainable, and socially responsible intelligent systems that align AI’s technical progress with goals of inclusion and environmental responsibility.